Clinical Updates in Women's Health Care Summary: The Role of Physical Therapy in Obstetric–Gynecologic Practice. Issue 3 (September 2018) - Butler, Rachel
Abstract : Abstract: This monograph addresses the diagnosis and management of many neuromusculoskeletal conditions that both obstetrician–gynecologists and physical therapists encounter in their practices. Collaborative care initiated by the physician through consultation with a physical therapist can considerably enhance women's health outcomes associated with these conditions. Physical therapy techniques are described to enhance physician understanding of the scope of this treatment option. Information is presented in the chronological sequence of a woman's reproductive life cycle, although some information is universal and affects multiple stages of a woman's life. Separate sections are devoted to problems of the pelvic floor muscles, pregnancy and postpartum care, and conditions common in older women.